2016
DOI: 10.1177/1744806916647055
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse traumatic brain injury induces prolonged immune dysregulation and potentiates hyperalgesia following a peripheral immune challenge

Abstract: BackgroundNociceptive and neuropathic pain occurs as part of the disease process after traumatic brain injury (TBI) in humans. Central and peripheral inflammation, a major secondary injury process initiated by the traumatic brain injury event, has been implicated in the potentiation of peripheral nociceptive pain. We hypothesized that the inflammatory response to diffuse traumatic brain injury potentiates persistent pain through prolonged immune dysregulation.ResultsTo test this, adult, male C57BL/6 mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 57 publications
4
27
0
1
Order By: Relevance
“…[17][18][19][20][21] Controlled cortical impact and fluid percussion injury models, procedures that need a craniotomy, induce comparable high cytokine expression. 12,[22][23][24] Because in a previous study we observed that approximately 30% of mice experienced skull fractures after WD injury (unpublished data), we hypothesize that injury to the skull may be one of the main triggers for the expression of inflammatory genes in the brain after WD injury and may thus contribute to the variability observed in this valuable TBI model. Therefore, the aim of the present study was to compare the inflammatory response after WD injury in the hippocampus and striatum of mice and correlate these findings with the presence and severity of skull fractures.…”
Section: Introductionmentioning
confidence: 86%
“…[17][18][19][20][21] Controlled cortical impact and fluid percussion injury models, procedures that need a craniotomy, induce comparable high cytokine expression. 12,[22][23][24] Because in a previous study we observed that approximately 30% of mice experienced skull fractures after WD injury (unpublished data), we hypothesize that injury to the skull may be one of the main triggers for the expression of inflammatory genes in the brain after WD injury and may thus contribute to the variability observed in this valuable TBI model. Therefore, the aim of the present study was to compare the inflammatory response after WD injury in the hippocampus and striatum of mice and correlate these findings with the presence and severity of skull fractures.…”
Section: Introductionmentioning
confidence: 86%
“…he peripheral nerves that communicate skin, muscle, and sensory organs with the brain must maintain functionality throughout life despite frequent stress and trauma [1][2][3][4][5][6] . Loss of integrity of peripheral neurons and associated cells, including glia, is a common occurrence in severe neurological dysfunctions that include weakness, pain, and loss of sensation 7 .…”
mentioning
confidence: 99%
“…CCL2 is one of chemokines that increases rapidly after various forms of experimental mTBI (37,38), contributing to secondary brain damage through attracting monocytes to sites of injury and in ammation (39). Moreover, mTBIinduced disruption of the blood-brain barrier (BBB)(40) allows the passage of in ammatory cells out of the injured brain, and initiates to an elevated systemic immune response to the genesis of nociceptor hypersensitivity post-TBI (11). Of particular interest is the nding of macroscopic GM hypertrophy in the dPCC (a core region in the DMN), which is related to the arousal, self-reference and breadth of attention (41), can mediate the contribution of circulating in ammatory biomarker (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…TBI can induce a multitude of in ammatory biomarkers perpetuating the secondary injury to the brain (7,8), which upregulates central nerve system (CNS) excitability contributing to the generation and persistent of concomitant headache (9)(10)(11). Multiple pain disorders have altered grey matter volume (GMV) within the pain matrix (12,13).…”
Section: Introductionmentioning
confidence: 99%